2011
DOI: 10.1021/la202804c
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Coalescence during Acoustic Cavitation in Aqueous Electrolyte Solutions

Abstract: Bubble coalescence behavior in aqueous electrolyte (MgSO(4), NaCl, KCl, HCl, H(2)SO(4)) solutions exposed to an ultrasound field (213 kHz) has been examined. The extent of coalescence was found to be dependent on electrolyte type and concentration, and could be directly linked to the amount of solubilized gas (He, Ar, air) in solution for the conditions used. No evidence of specific ion effects in acoustic bubble coalescence was found. The results have been compared with several previous coalescence studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 53 publications
2
56
0
Order By: Relevance
“…In acoustical cavitation experiments Sunartio et al (2007) show that the average cavitation bubble size is reduced by adding sodium dodecyl sulfate, simultaneously less coalescence is observed at lower surface tensions (Lee et al, 2007). By addition of an electrolyte like sodium chloride a similar reduced coalescence behavior of cavitation bubbles is reported (Browne et al, 2011). Further on, acoustic cavitation damage caused by collapsing bubbles decreases with lowered surface tension (Iwai and Li, 2003), which indicates a reduced energy dissipation during the collapse of cavities.…”
Section: Theoretical Backgroundmentioning
confidence: 78%
“…In acoustical cavitation experiments Sunartio et al (2007) show that the average cavitation bubble size is reduced by adding sodium dodecyl sulfate, simultaneously less coalescence is observed at lower surface tensions (Lee et al, 2007). By addition of an electrolyte like sodium chloride a similar reduced coalescence behavior of cavitation bubbles is reported (Browne et al, 2011). Further on, acoustic cavitation damage caused by collapsing bubbles decreases with lowered surface tension (Iwai and Li, 2003), which indicates a reduced energy dissipation during the collapse of cavities.…”
Section: Theoretical Backgroundmentioning
confidence: 78%
“…For small values of viscosity (~1 -3 cp) there is a varied relation to coalescence time, however for a large viscosity it is clear that the coalescence time increases. This could imply that highly viscous fluids inhibit bubble surface motion and film drainage between the bubbles in contact, which is known to reduce coalescence [213]. However, the time for coalescence to occur becomes relevant in an ultrasound environment due to time dependant forces on the bubbles [36].…”
Section: Surface Tension and Viscositymentioning
confidence: 99%
“…Several authors have recognised the ability of electrolyte solutions to influence the size of bubbles during sonication, the severity of collapse and coalescence [162,[211][212][213]251]. There are two suggestions as to the electrolytes' effect.…”
Section: Salt Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, they indicated that acoustic intensity was more important than other factors. As to the microcosmic mechanism, current researches are mainly about the characteristics of cavitation bubbles under ultrasonic field, while few works reported the mechanism of ultrasonic demulsification [20][21][22][23][24][25][26][27]. However, the physical properties between oil-water system and gas-liquid system are significantly different.…”
Section: Introductionmentioning
confidence: 99%